ANALYSIS OF INSTAGRAM CONTENT MANAGEMENT FOR GEPREK BENSU DIGITAL PROMOTION - Salsabila Ahmad; Bella Maulidiya; Achmad Muhajir; Badriyah (POLITEKNIK LP3I JAKARTA, 2026)
This study was conducted to analyze the use of Instagram as a digital marketing medium to increase sales at Geprek Bensu. The research employs a descriptive method with a qualitative approach. Data were obtained through observation of the Instagram account @geprekbensu, supported by relevant journals and scientific articles. The analysis covers the number of followers, likes, comments, and the consistency of content posting from January to December 2025. The findings indicate that the Geprek Bensu Instagram account has a substantial number of followers, namely 816 thousand, giving it high potential as a digital promotional medium. However, the level of audience interaction with the uploaded content remains relatively low, with an average engagement rate of 0.010%. In addition, an inconsistent posting frequency prevents the digital marketing effort from operating optimally. A more effective marketing strategy is therefore needed, one that improves content quality, maximizes the use of Instagram's features, and establishes a regular posting schedule in order to increase audience interaction and support sales growth. With proper management, Instagram can serve as an effective marketing medium for expanding promotional reach and increasing Geprek Bensu's sales.